The Impact of Traffic Congestion on Roads: A Highway Case Study Ligung-Majalengka - Muhammad Taufik Ivan Syaepudin; Muhammad Taufik; Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2025)
Traffic congestion has become an increasingly complex and pressing global problem. Rapid population growth, rapid urbanization, and increasing private vehicle ownership have greatly increased traffic volumes in a number of cities in various parts of the world. This study aims to determine problems related to road density and congestion in the context of infrastructure development and urbanization. This paper discusses the problem of road density. The Ligung highway is usually busy during rush hours, which often occurs in the morning and also in the afternoon. This situation is caused by the working hours of factory employees and children going to school in the morning and returning home at the same time in the afternoon. The location of this research is in Ligung, which is on Jalan Raya Ligung which will lead to the Jatiwangi-Kadipaten road ± 1000 meters. This writing focuses on speed and density analysis to help determine the average vehicle speed and average vehicle density. Apart from using qualitative methods, field observations were also carried out to determine and detect the volume of highways, vehicles passing, and the speed of vehicles passing, how congested the highway was. Ligung. Primary data consists of the number of vehicles passing, Microsoft Excel 2021 and Traffic Counter software. Secondary data is MKJI 1997. For data, the highway section consists of a road through two opposing traffic lanes (2/2 UD). The level of congestion and density of traffic conditions on the surveyed roads are also displayed using speed and density data. To obtain information on traffic density and road performance in the area, these parameters must be observed and analyzed further.